The Role of Work-Life Balance in Mediating the Relationship Between Job Satisfaction and Organizational Commitment Among Working Students - Koen Hendrawan; Hamidah Hamidah; Hania Aminah; Antoni Ludfi Arifin (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2025)
This study aims to analyze the role of work-life balance in mediating the relationship between job satisfaction and organizational commitment among working students. The research sample consists of 103 respondents selected using a convenience sampling technique. Data were collected through questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the hypotheses and mediation effects. The results indicate that job satisfaction positively influences work-life balance and organizational commitment. Furthermore, work-life balance also has a significant positive effect on organizational commitment. Mediation analysis shows that work-life balance fully mediates the relationship between job satisfaction and organizational commitment. These findings highlight the importance of work-life balance in enhancing organizational commitment among working students, suggesting that organizations should prioritize policies and programs that support work-life balance to foster a more committed workforce. This study contributes theoretically by enriching the literature on work-life balance, job satisfaction, and organizational commitment, particularly within the unique context of working students. Practically, it offers valuable insights for human resource management in developing effective strategies to improve employee well-being and organizational loyalty.